PENGEMBANGAN IMPLEMENTASI PENGGUNAAN AUGMENTED REALITY PADA APLIKASI GAMES TEBAK NAMA, SUARA, MAKANAN HEWAN BERBASIS ANDROID - Muhammad Noval Riswandha; Sukma Nova Alviosara (SPIRIT, 2023)
Abstract : With the technology in Indonesia, which is currently growing rapidly. In the past, the delivery of information was still using 2D images, now the media for delivering information can use 3D images so that the information provided is clearer and more effective. Many people prefer Android phones because they are easy to use and relatively inexpensive. The use of Augmented Reality on Android is to design applications by displaying various kinds of 3D animal images as learning media or tools that can support the teaching and learning process and increase the creativity of students by introducing names, sounds, and animal food with current technology. The learning process using Augmented Reality technology with the Multimedia Development Life Cycle (MDLC) method and Android-based Iterative Rapid Prototyping is an option that can be done by anyone, anywhere and anytime. This application is not only for teaching teachers but also by the general public and is easy to run.